2005
DOI: 10.1111/j.1365-2222.2005.02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil infiltration of the oesophageal mucosa in patients with pollen allergy during the season

Abstract: Thirty-eight symptomatic patients (allergic rhinitis (AR) with or without asthma) who had sensitization to grass pollen were included in the study during the pollen season. Controls were composed of 25 healthy non-atopics and 24 patients diagnosed as having gastro-oesophageal reflux disease. Reflux was excluded in allergic and non-atopic groups, whereas the presence of allergy was eliminated in control groups. Gastrointestinal endoscopy was performed in all participants, and biopsy specimens were taken from bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 40 publications
6
47
1
1
Order By: Relevance
“…5 Further evidence for seasonality of EoE symptoms and esophageal eosinophilia has been described in other studies. Onbasi et al 6 found that 26% of patients with allergic rhinitis without GERD had esophageal eosinophilia at biopsy examination during a time of active allergy symptoms. Wang et al 7 found that significantly fewer cases of EoE were diagnosed in children during the winter season compared with spring, summer, and fall.…”
Section: Introductionmentioning
confidence: 98%
“…5 Further evidence for seasonality of EoE symptoms and esophageal eosinophilia has been described in other studies. Onbasi et al 6 found that 26% of patients with allergic rhinitis without GERD had esophageal eosinophilia at biopsy examination during a time of active allergy symptoms. Wang et al 7 found that significantly fewer cases of EoE were diagnosed in children during the winter season compared with spring, summer, and fall.…”
Section: Introductionmentioning
confidence: 98%
“…Another explanation may be related to the systemic immune response of allergens. Once a susceptible patient is exposed to an allergen, the bone marrow increases eosinophil production with subsequent migration of eosinophils to the esophagus in patients with EoE, similar to the migration of eosinophils to the airways in asthmatics [27,28].…”
Section: Pathogenesismentioning
confidence: 96%
“…The patients with EoE we studied had a clinical presentation including the symptoms, such as heartburn, food impaction, and dyspepsia, that were validated by the Mayo dysphagia questionnaire [14]. Both inhalant and food allergens seem to play a role in the pathophysiology of EoE [18], as demonstrated for aeroallergens in experimental animal models, while in humans it was suggested by the fact that eosinophil infiltration may be observed in esophageal tissue of patients with respiratory allergy during the symptomatic period [19,20]. The important role of food allergens in EoE was shown by an improvement of symptoms and resolution of histological abnormalities after specific elimination diets [21][22][23].…”
Section: Discussionmentioning
confidence: 99%